2011
DOI: 10.1177/175114371101200109
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Poisoning with Glyphosate-Surfactant Herbicide

Abstract: A 29-year-old man was admitted following the deliberate (witnessed) ingestion of approximately 300 mL of 'Roundup Ace,' a herbicide containing glyphosate as its active ingredient. On presentation he was agitated and sweating, with partial airway obstruction and trismus. He required intubation and mechanical ventilation for airway control.Initial blood gases were normal but within a few hours of admission he had developed a severe and persistent lactic acidosis. A continuous sodium bicarbonate infusion was comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The spectrum of GlySH poisoning includes minimal irritation of eyes to severe as shock and death. [ 1 ] Severe poisoning causes dehydration, hypotension, pneumonitis, oliguria, altered level of consciousness, hepatic dysfunction, acidosis, hyperkalemia, and dysrhythmias. [ 3 ] The clinical manifestations are determined by volume of surfactant ingested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of GlySH poisoning includes minimal irritation of eyes to severe as shock and death. [ 1 ] Severe poisoning causes dehydration, hypotension, pneumonitis, oliguria, altered level of consciousness, hepatic dysfunction, acidosis, hyperkalemia, and dysrhythmias. [ 3 ] The clinical manifestations are determined by volume of surfactant ingested.…”
Section: Discussionmentioning
confidence: 99%
“…Severe GlySH-surfactant poisoning is manifested by gastroenteritis, respiratory disturbances, altered mental status, hypotension refractory to the treatment, renal failure, and shock. [ 1 ] GlySH intoxication has a case fatality rate 3.2–29.3%. Pulmonary toxicity and renal toxicity seem to be responsible for mortality.…”
mentioning
confidence: 99%
“…Severe glyphosate-surfactant poisoning is manifested by gastroenteritis, respiratory disturbances, altered mental status, treatment-resistant hypotension, renal failure and shock [137]. The fatality rate ranges from 3 to 30%, and is mostly due to either pulmonary toxicity or renal failure.…”
Section: Tyrosine Phosphatase and Systemic Inflammationmentioning
confidence: 99%
“…Nevertheless, it is worth mentioning that Fuller’s earth (magnesium citrate) and charcoal have similar effects[ 18 ], and there is no need for their simultaneous prescription. Although some of the old studies had proposed the necessity for gastric lavage in paraquat poisoning[ 19 , 20 ], Wilks et al[ 21 ] showed that gastric lavage can lead to increase in mortality rate in cases where the patient has consumed lesser than 30 cc of poison. It seems that gastric cleansing was inappropriate in the studied patients.…”
Section: Discussionmentioning
confidence: 99%